Water Sorption and Desorption of Isolated Cuticles From Three Woody Species With Focus on Ilex aquifolium - Vega, Clara; Valbuena-Carabaña, María; Gil, Luis; Fernández, Victoria (Frontiers in Plant Science, 2021)
The cuticle is a lipid-rich layer which protects aerial plant organs against multiple stress factors such as dehydration. In this study, cuticle composition and structure in relation to water loss are examined in a broad ecophysiological context, taking into consideration leaf age and side from Ilex aquifolium (holly) in comparison to Eucalyptus globulus (eucalypt) and Prunus laurocerasus (cherry laurel). Enzymatically isolated cuticular membranes from holly leaves were studied under three treatments: natural (no chemical treatment), after dewaxing and after methanolysis and their rate of water loss was assessed. Structural and chemical changes were evaluated by using different microscopy techniques and Fourier Transform Infrared spectroscopy (FTIR). The potential mechanisms of solute absorption by holly leaves were additionally evaluated, also testing if its prickly leaf margin may facilitate uptake. The results indicate that treatments led to structural changes while chemical composition was hardly affected due to the occurrence of cutan. Structural changes led to more hydrophilic adaxial surfaces, which retained more water and more efficiently than natural cuticles, while changes were not significant for abaxial surfaces. Across natural cuticles, age was only a significant factor for eucalypt and not for holly. Young eucalypt cuticles were the group that absorbed more water and had the lowest water loss rate. When comparing older leaf cuticles of the three species, cherry laurel was found to absorb more water which was however lost more slowly, compared to the other species. Evidence was gained that holly leaves can absorb foliar-applied solutes (traced after calcium chloride application) through the adaxial and abaxial surface, the adaxial midveins and to a lower extent, via the spines. In conclusion, for the species examined, our results show variations in leaf cuticle composition and structure in relation to leaf ontogeny and water sorption and desorption capacity.